Constant chemical potential cycles for capacitive deionization. Issue 44 (30th October 2019) - Moreno, Daniel; Hatzell, Marta C.
Abstract : The thermodynamic path followed during an electrosorption, desorption and solution-switching process, influences the energy consumed per ion removed. Abstract : The primary energy consuming operations which occur within a Capacitive Deionization (CDI) cell, are the ion removal (electrosorption), ion concentrating (electrodesorption), and solution switching processes. In theory the maximum system performance for a CDI system arises when solution switching occurs while maintaining a fixed number of ions ( N ), and when electrosorption/desorption occurs while maintaining a fixed chemical potential ( μ ). These fixed state variable based operations are analogous to the Carnot cycle, where heat transfer occurs at constant temperature and compression and expansion occur while maintaining constant entropy. In reality, maintaining a constant number of ions during switching is not practically feasible, thus here we investigate two alternative cycles where switching instead occurs while maintaining constant charge or voltage. Unlike constant number of ions, maintaining charge and voltage constant is feasible using a potentiostat. These theoretical cycles were chosen as they are analogues or ideal-like (Stirling and Ericsson) cycles, which are also practically feasible. The thermodynamic analysis reveals that these alternative cycles provide an avenue to approach the theoretical limit with low saline feed water; however, they are not capable of approximating ideal operations at elevated feed-water concentrations.